PEMBERDAYAAN PENDERITA KUSTA DENGAN KECACATAN DERAJAT 2 DAN KELUARGANYA DALAM REHABILITASI DAN PERAWATAN DIRI SECARA MANDIRI - Puspasari, Ni Made Indah; Dewi, Liana; Amukty, Octora Young (JURNAL SEWAKA BHAKTI, 2024)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae. Leprosy is the main cause of permanent physical disability. Defects in the hands and feet are divided into three levels of disability according to WHO (1988), level 0 (no anesthesia and anatomical abnormalities), level 1 (anesthesia, no anatomical abnormalities) and level 2 (anatomical abnormalities). There is no effective therapy for leprosy disability, so holistic therapy such as medical rehabilitation is needed. The Community Partnership Program (PKM) partner is a leprosy sufferer, a 63 years old woman with grade 2 disability and her family. The patient also experienced paralysis in both legs due to a stroke which was a complication of the diabetes mellitus. The method for implementing PKM activities is by providing training on self-rehabilitation and self-care so that complications due to leprosy disability can prevented, and providing wheelchairs to help partners mobilize. Indicators of achievement include moist extremity skin, no new wounds appearing, contractures on the patient's hands and both of legs not getting worse and the patient getting a wheelchair has reached 100%.